A unique case of well differentiated papillary mesothelioma involving an inguinal hernia - T N Anirudhan; Ranjani Chakravarthy; P Jothishankar (Wolters Kluwer Medknow Publications, 2012)
Well Differentiated Papillary Mesothelioma (WDPM) is an uncommon tumor occurring predominantly in the peritoneum of young women with no history of asbestos exposure. In this report, we present a case of 48 year old male patient presenting with indirect inguinal hernia and incidental finding of a WDPM in the hernial sac during surgery. The unusual site of presentation and the relative rarity of this neoplasm in males evoke much clinico-pathological interest.